1887 Fla. Laws 164-165, An Act to Establish the Municipality of Jacksonville Provide for its Government and Prescribe it’s jurisdiction and powers, chap. 3775, § 4 - (:unkn) unknown (General Publisher, 1887)
Granted the city of Jacksonville the authority to regulate and license the sale of firearms and suppress the carrying of concealed weapons.
--
Keywords: CARRY - CONCEALED